Sodium Propionate Enhances Nrf2-Mediated Protective Defense Against Oxidative Stress and Inflammation in Lipopolysaccharide-Induced Neonatal Mice - Chen D (Dove Medical Press, 2021)
Dan Chen,1,* Zhi-qi Gao,1,* Ying-ying Wang,1 Bin-bin Wan,1 Gang Liu,1 Jun-liang Chen,1 Ya-xian Wu,1 Qin Zhou,2 Shan-yu Jiang,2 Ren-qiang Yu,2 Qing-feng Pang1 1Department of Physiopathology, Wuxi School of Medicine, Jiangnan University, Wuxi, 214122, Jiangsu Province, People’s Republic of China; 2Department of Neonatology, The Affiliated Wuxi Maternity and Child Health Care Hospital of Nanjing Medical University, Wuxi, 214002, Jiangsu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ren-qiang Yu 48 Huaishu Lane, Liangxi District, Wuxi, Jiangsu Province, People’s Republic of ChinaTel +86510-82709790Fax +86-510-82725094Email yurenqiang553@163.comQing-feng Pang 1800 Lihu Avenue, Binhu District, Wuxi, Jiangsu Province, People’s Republic of ChinaTel +8651052430172Fax +86-510-85329042Email qfpang@jiangnan.edu.cnBackground: Alveolar arrest and the impaired angiogenesis caused by chronic inflammation and oxidative stress are two main factors in bronchopulmonary dysplasia (BPD). Short-chain fatty acids (SCFAs), especially propionate, possess anti-oxidant and anti-inflammatory effects. The present study was designed to examine the roles of sodium propionate (SP) on lipopolysaccharide (LPS)-challenged BPD and its potential mechanisms.Methods: WT, Nrf2-/- mice and pulmonary microvascular endothelial cells (HPMECs) were used in this study. LPS was performed to mimic BPD model both in vivo and vitro. Lung histopathology, inflammation and oxidative stress-related mRNA expressions in lungs involved in BPD pathogenesis were investigated. In addition, cell viability and angiogenesis were also tested.Results: The increased nuclear factor erythroid 2-related factor (Nrf2) and decreased Kelch-like ECH-associated protein-1 (Keap-1) expressions were observed after SP treatment in the LPS-induced neonatal mouse model of BPD. In LPS-induced wild-type but not Nrf2-/- neonatal mice, SP reduced pulmonary inflammation and oxidative stress and exhibited obvious pathological alterations of the alveoli. Moreover, in LPS-evoked HPMECs, SP accelerated Nrf2 nuclear translocation presented and exhibited cytoprotective and pro-angiogenesis effects. In addition, SP diminished the LPS-induced inflammatory response by blocking the activation of nuclear factor-kappa B pathway. Moreover, pretreatment with ML385, an Nrf2 specific inhibitor, offsets the beneficial effects of SP on inflammation, oxidative stress and angiogenesis in LPS-evoked HPMECs.Conclusion: SP protects against LPS-induced lung alveolar simplification and abnormal angiogenesis in neonatal mice and HPMECs in an Nrf2-dependent manner.Keywords: sodium propionate, lipopolysaccharide, Nrf2, angiogenesis, bronchopulmonary dysplasia